(3YbO Yed cQI GdbOe Ydi Vh GdNUhUjI GdQjGVjI (B: (3OGSI MGdI HYV fhGOj cQI GdbOe GdeMJQaI h GdgGhjI ddbSe GdhWfj GdGhd GdeJhGLOI HGdYGUeI s - (3HhgdI , MajXs; (3HhQfGf, TQja eUWais; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2020)
(3JYed fhGOj cQI GdbOe Ydi JMSjf COGA CeKd ddGYHjgG HEYOGO GdhSGFd hJgjFI LejY GdXQha hGdCSHGH GdG Gfg dG jecf Gf jJCJi Pdc GdG ef NdGd GdGSJYGfI HGdeOQHjf GdCcKQ caGAI dJOQjH aQbge ef GLd GdGQJbGA HeSJhj dGYHjge dVeGf GdahR HGdHWhdGJ, GdJj jfLQ YfgG GdMUhd Ydi ehGQO eGdjI gGeI JJeGTi eY GSJKeGQGJgG GdeGdjI(B. (3hdeG cGfJ GdYedjI GdJOQjHjI fTGWG egfjG eMVG heCLhQG jSJdRe GdJfXje adG jecf Gf jchf Pdc GdG Yf WQjb GHQGe YbO Yed Hjf GdeOQH GdQjGVj dcQI GdbOe hGdfGOj GdQjGVj, ShGA GcGf fGOj QjGVj eMJQa Gh fGOj QjGVj gGhj, hHGdJGdj aGf YdGbI Yed eOQH cQI GdbOe eY GdfGOj GdQjGVj JNVY aj hLhOgG Gdi GMcGe hbhGYO bGfhf GdYed cZjQgG ef YdGbGJ GdYed(B. (3dcf jHOh LdjG HGf GdeeGQSGJ GdYbOjI GdQjGVjI gj YdGbGJ aQjOI ef fhYgG dG eKjd dgG aj ZjQgG ef YdGbGJ GdYed GdCNQi eeG SjDKQ MJeG Ydi GdEWGQ GdYGe hGdbGfhfj dgPg GdYbhO hcjajI GNVGYgG dCMcGe bGfhf GdYed (B90-11 (3hGdbhGYO GdeWHbI Ydi GdYeGd GdcdGSjcjjf GdYGedjf aj GdbWGY GdGbJUGOj, hYdjg jLH GdGNP HYjf GdGYJHGQ WHjYI GdfTGW GdQjGVj GdPj JfJL Yfg gPg GdeeGQSGJ GdNGUI GdJj dG eKjd dgG aj ZjQgG ef YdGbGJ GdYed GdCNQi(B. s
(3OcJhQGgs
Keywords: (3GdJTQjY GdQjGVjs; (3GdYbO GdQjGVjs; (3JSjjQ GdefTBJ GdQjGVjI h GdehGQO GdHTQjIs